Best of my love [compact disc, unabridged] - Mallery, Susan (Mallery, Susan. Fool's gold, 2016)
To overcome her painful past, baker Shelby Gilmore goes on the hunt for a friend, a male friend, to convince her stubborn psyche that men can be trusted. But where in a town as small as Fool's Gold will the petite blonde find a guy willing to not date her? Dark, charming Aidan Mitchell puts the 'adventure' in Mitchell Adventure Tours, and into the beds of his many willing female tourists. Maybe Shelby's boy/girl experiment will help him see women as more than just conquests so he can change his ways and win back his self-respect.